Implementasi Media Pembelajaran Augmented Reality (AR) terhadap Pengenalan Huruf Arab Pada Anak Usia Sekolah Dasar di Wafa English Crouse Lhokseumawe - Alvia Khaira; Ferry Rusda (Ameena Journal, 2026)
The introduction of Arabic letters still faces challenges in improving students’ motivation and understanding, especially among elementary school-aged children. The importance of introducing hijaiyah letters requires interactive learning media. This study aims to implement Augmented Reality (AR)-based learning media for the introduction of hijaiyah letters and to analyze students’ responses and learning interest toward the media. The method used in this study is a case study method within qualitative research. The subjects of this study were 10 students at Wafa English Course. The data were collected through observation, interviews, and documentation. The results show that the learning process was active and interactive. Augmented Reality (AR) media was proven to increase students’ learning interest and help them understand the shapes and pronunciation of Arabic letters more easily. Therefore, Augmented Reality (AR) media is recommended as an effective learning innovation for elementary education.